An Investigation of the Antidepressant Action of Xiaoyaosan in Rats Using Ultra performance Liquid Chromatography–Mass Spectrometry Combined with Metabonomics. (13th September 2012) - Gao, Xiao‐Xia; Cui, Jie; Zheng, Xing‐Yu; Li, Zhen‐Yu; Choi, Young‐Hae; Zhou, Yu‐Zhi; Tian, Jun‐Sheng; Xing, Jie; Tan, Xiao‐Jie; Du, Guan‐Hua; Qin, Xue‐Mei
Abstract : A rapid, highly sensitive, and selective method was applied in a non‐invasive way to investigate the antidepressant action of Xiaoyaosan (XYS) using ultra performance liquid chromatography–mass spectrometry (UPLC‐MS) and chemometrics. Many significantly altered metabolites were used to explain the mechanism. Venlafaxine HCl and fluoxetine HCl were used as chemical positive control drugs with a relatively clear mechanism of action to evaluate the efficiency and to predict the mechanism of action of XYS. Urine obtained from rats subjected to chronic unpredictable mild stress (CUMS) was analyzed by UPLC‐MS. Distinct changes in the pattern of metabolites in the rat urine after CUMS production and drug intervention were observed using partial least squares–discriminant analysis. The results of behavioral tests and multivariate analysis showed that CUMS was successfully reproduced, and a moderate‐dose XYS produced significant therapeutic effects in the rodent model, equivalent to those of the positive control drugs, venlafaxine HCl and fluoxetine HCl. Metabolites with significant changes induced by CUMS were identified, and 17 biomarker candidates for stress and drug intervention were identified. The therapeutic effect of XYS on depression may involve regulation of the dysfunctions of energy metabolism, amino acid metabolism, and gut microflora changes. Metabonomic methods are valuable tools for measuring efficacy and mechanisms of action in the study of traditional Chinese medicines. Copyright © 2012 John Wiley & Sons, Ltd.